The perspectives of university guidance staff about the development of guidance services - Rantanen, Jasmin (2021)
Societal changes require the university guidance services to develop. Constant change and uncertainty in working life, the modularization of higher education and individual study paths as well as digitalization, internationalization, and the ideology of lifelong learning challenge guidance services. The most recent national evaluations and follow-up studies of university guidance processes in Finland were conducted in the early 2000s. The aim of this study is to broaden research on the state of the Finnish university guidance service entity at the turn of the 2020s, especially from the perspective of university guidance staff. The main research question was: How do the staff of centralized university guidance services perceive the need for the development of university guidance services and the factors that affect those changes? The data were collected through focus group interviews and analyzed using a theory-driven content analysis approach. Based on the results, the guidance services of Finnish universities are influenced by multiple parties and development efforts are needed at different levels and dimensions of the guidance system. The service entity of the university guidance system must be developed to respond to changes and demands in the society.